IMPLEMENTASI METODE FORENSIK JARINGAN UNTUK MEMONITORING KOMPUTER WINDOWS SERVER - Mahendra, Brian Abimayu; Utomo, Yudo Bismo; Kurniadi, Harso (JUKOMPSI (Jurnal Komputer dan Sistem Informasi), 2024)
The use of global computer networks, such as the internet, makes it easier to complete various jobs. However, this convenience also triggers misuse of unauthorized access to commit certain crimes. To prevent this, network administrators need to implement strategies to ensure the network remains safe from unauthorized access. One commonly used network security system is a firewall, which functions to protect data from users who do not have access rights. One type of attack that often occurs is a Denial of Service (DoS) attack which aims to drain computer resources by targeting the Windows server in an agency, so that other users have difficulty accessing the computer being attacked. In maintaining the integrity, confidentiality and availability of data, monitoring network security is a crucial aspect. This research proposes the use of network forensic methods for network traffic analysis in detecting and responding to security incidents. This research uses Wireshark, a network traffic analysis tool, to detect Distributed Denial of Service (DDoS) attacks. Wireshark is able to capture and examine data packets passing through the network, so it can identify DDoS attack patterns such as abnormal traffic spikes and suspicious packets. Through DDoS attack simulations, this research shows how network forensic methods can be used effectively to detect, analyze and respond to cyber attacks.